Unusual occurrence of diving accidents : Case reports from andaman & nicobar islands - S S Mohapatra; A K Anand; C S Mohanty; Swaroop Pathnaik; Bhavni Oberoi; Sargundeep Singh (Journal of Marine Medical Society, 2015)
Introduction: Andaman and Nicobar islands due to their unique location offer several exclusive diving sites and form a hub of recreational SCUBA diving and commercial diving. This in turn increases the possibility of diving accidents in these areas. Seven cases with a wide spectrum of presentations and rare symptoms has been compiled in this article. Observations : Six cases of “Decompression Sickness” which is rare type of diving accidents in the recent times, were reported with rare and varied symptoms. Out of six cases of DCS, four were type 2 with varied presentations due to neurological, cerebellar, pulmonary etc. involvement and only one case was type 1 with skin involvement. Joint manifestation which is the common form of DCS (popularly known as “Bends”) was not reported. A thorough history, good clinical examinations, advice from Marine Medicine Specialists and prompt administration of Recompression therapy were the key factors for successful recovery of such cases. Conclusions: Management of Decompression Sickness (DCS) can be extremely challenging both in the pre-hospital and hospital care setup. This could be convoluted further by lack of hyperbaric chamber and trained staff. Availability of a Recompression chamber (RCC) has been a boon in remote areas where such cases are common.